STUDENTS’ PERCEPTION TOWARDS THE USE OF OMEGLE TO ENHANCE ENGLISH SPEAKING SKILL - Asaika, Genada (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2023)
This study aimed to find out the students’ perception toward the use of Omegle as learning media to enhance their English speaking skills. Omegle is a free communication platform that may connect individuals from various ethnicities and countries for one-on-one dialogue. Omegle users generally use English to interact with each other since English is a lingua franca and has a majority of speakers around the world. Respondents of this study were English Language and Literature students at Universitas Airlangga who used Omegle. The results of this study found that undergraduate students of Universitas Airlangga have a positive perception of systems in Omegle and are interested in its use for improving their English speaking skills. Therefore, the researchers suggest that future work may be able to include the development of a prototype for interactive learning media that assist and provide useful feedback for students in improving their English skills.